The Impact of Lebrikizumab on Vaccine-Induced Immune Responses: Results from a Phase 3 Study in Adult Patients with Moderate-to-Severe Atopic Dermatitis - Jennifer Soung; Vivian Laquer; Joseph F. Merola; Angela Moore; Hany Elmaraghy; Chaoran Hu; Maria Lucia Buziqui Piruzeli; Evangeline Pierce; Esther Garcia Gil; Abel D. Jarell (Adis, Springer Healthcare, 2024)
Abstract Introduction Lebrikizumab, a high-affinity IgG4 monoclonal antibody that selectively inhibits interleukin-13 with high binding affinity and slow dissociation rate, prevents the formation of the interleukin-4Rα/interleukin-13Rα1 heterodimer receptor signaling complex. Here we report the impact of lebrikizumab on responses to two non-live vaccines in adult patients with moderate-to-severe atopic dermatitis (AD). Methods ADopt-VA (NCT04626297) was a double-blind, placebo-controlled, parallel-group, 16-week, phase 3 randomized study to assess the impact of lebrikizumab treatment on non-live vaccine immune responses, and efficacy and safety of lebrikizumab compared with placebo. Eligible patients included adults from 18 to 55 years of age with moderate-to-severe chronic AD who were randomly assigned 1:1 to lebrikizumab 250 mg every 2 weeks or placebo and stratified according to disease severity. The primary endpoints were the development of a booster response to tetanus toxoid and a positive antibody response to meningococcal conjugate vaccine (MCV), 4 weeks after administration of the corresponding vaccine. Results At week 16, 73.6% of patients in the lebrikizumab group (n = 78/106) achieved Tdap booster response compared with 73.4% of patients in the placebo group (n = 58/79). MCV vaccine response was observed in 86.9% of patients in the lebrikizumab group (n = 86/99) and 75.0% of patients in the placebo group (n = 60/80). At week 16, IGA 0,1 with ≥ 2-point improvement from baseline was achieved by 40.6% (n = 51/125) of patients treated with lebrikizumab and 18.9% (n = 23/122) of patients who received placebo (p < 0.001). There was a higher proportion of patients achieving EASI 75 at week 16 in the lebrikizumab-treated patients (58.0%, n = 72/125) compared with placebo (32.7%, n = 40/122, p < 0.001). Conclusions Treatment with lebrikizumab did not impact response to non-live vaccines Tdap and MCV in this study. Lebrikizumab treatment had a significant degree of efficacy compared to placebo across multiple endpoints. Trial Registration ClinicalTrials.gov identifier NCT04626297.